Analysis of Category Theory as a General Framework for Algebraic and Applied Structures - Nuraisah, Siti; Harahap, Amin; Harahap, Nurlina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Category theory is one of the important frameworks in modern mathematics because it is able to unify various algebraic concepts and structures. In addition, this theory has been widely applied in many other fields. This article aims to provide a comprehensive discussion of the role of category theory as a universal language that not only explains relationships among mathematical objects, but also serves as a methodological foundation for computer science, logic, and data science. This study employs a qualitative approach through a literature review by examining key concepts such as objects, morphisms, functors, adjunctions, and monads, as well as their roles in bridging abstract theory and practical applications. The results of the literature review indicate that category theory is capable of simplifying the complexity of algebraic structures through a higher level of abstraction. Through this approach, different branches of mathematics that were previously fragmented can be interconnected. Furthermore, category theory has been widely used in functional programming, the development of logic-based systems, and data flow modeling, making it highly relevant in the digital era. The research approach involves literature review, content analysis, and triangulation to ensure data validity, with the implication that category theory can enrich teaching and research in the field of algebra.